Photoswitching Proteins: methods and protocols - Cambridge, Sidney (Methods in molecular biology, 2014)
Photoinduced Damage Resulting from Fluorescence Imaging of Live Cells -- Modification of Purified Proteins with Photochemical Protection Compounds for High-Resolution Photoactivation of Protein Function In Vitro and In Vivo -- Optochemical Activation of Kinase Function in Live Cells -- Photoswitching of Cell Surface Receptors Using Tethered Ligands -- Photocontrol of AMPA Receptors with a Photochromic Ligand -- Photoconversion of CFP to Study Neuronal Tissue with Electron Microscopy -- Light-Inducible Gene Regulation with Engineered Zinc Finger Proteins -- Manipulation of Plasma Membrane Phosphoinositides using Photoinduced Protein-protein Interactions -- A Roadmap to Applying Optogenetics in Neuroscience -- Salvaging Ruins: Reverting Blind Retinas into Functional Visual Sensors -- Photoactivated Adenylyl Cyclases as Optogenetic Modulators of Neuronal Activity -- Structural Basis of Photoswitching in Fluorescent Proteins -- Using Photoactivatable GFP to Track Axonal Transport Kinetics -- In Vivo Cell Tracking Using PhOTO Zebrafish -- In vivo Optogenetics for Light-induced Oxidative Stress in Transgenic Zebrafish Expressing the KillerRed Photosensitizer Protein -- Photoactivatable Fluorescent Proteins for Super-Resolution Microscopy -- pcSOFI as a Smart Label-based Superresolution Microscopy Technique.